Overview of School Sanitation Facilities Readiness During The Corona Virus Disease 19 Pandemic - Hairil Ikhwan Saputra; Yustini Ardillah (Jurnal Berkala Kesehatan, 2021)
Corona Virus Disease (COVID-19) is a virus that can spread rapidly from human to human. Adequacy of Sanitation Facilities will support the process of preventing transmission. The plan to reopen schools will have the potential to become a cluster of COVID-19 transmission, if not supported by adequate sanitation facilities.The research objective was to analyze the readiness of school sanitation facilities related to CTPS facilities in the prevention of COVID-19 at SMK Negeri 1 Lubuk Linggau city.This study is a qualitative descriptive study with an observational approach. Information is obtained through in-depth interviews, observation, and document review. The data analysis used is content analysis with the triangulation method. The results showed that the CTPS facility was available but not equipped with a sink, no drying equipment, and the conditions were poorly maintained. The provision of hand sanitizer-based CTPS facilities has been budgeted for with BOS funds. In the implementation of CTPS, there are still school members who do not know how to wash their hands properly and correctly. The school has prepared spare masks, thermogenic as an effort to prevent COVID-19. The implementation of COVID-19 prevention has not been optimal because there are still school residents who do not optimally implement health protocols in education units.